Sosialisasi Literasi Keuangan Syariah Pada Anak Usia Dini - Peni Haryanti; Athi’ Hidayati; Iesyah Rodliyah; Choirun Nisful Laili; Sari Saraswati (University of Islam Malang, 2020)
Indonesia is a country with a majority Muslim population. In terms of quantity, it has big potential as a center for the development of Islamic finance. The lack of Islamic financial literacy has made the public do not understand the importance of Islamic financial institutions in terms of both the benefit of the world and the hereafter. The method of implementing this activity is carried out in four stages, namely (1) Planning, (2) Preparation, (3) Implementation, and (4) Evaluation Implementation. At the implementation stage, socialization of sharia financial literacy is carried out to students, teachers and guardians of students and mentoring. The results obtained from community service are the first percentage of understanding and knowledge of financial literacy which increased from 56,5% to 85% both students, teachers and guardians of students viewed from the results of the pretest and posttest that have been given. Secondly, during the mentoring the participants gave a positive response with a percentage of 86% and 100% interested in participating in the second phase of socialization in order to know the positive developments after obtaining mentoring as seen from the results of the questionnaire responses that had been given.